The 15th Century Palace Architecture of Ferrara in the Context of the Venetian Architectural Tradition:The Oriental Aspect - Smagol, Oxana S. (Actual Problems of Theory and History of Art, 2017)
The 15th century palace architecture of Ferrara provides one of special examples of the so-called “synthetic style” in the second half of the Italian Quattrocento. It emerged from the overlapping of local architectural language and some traits of Lombard and Venetian traditions. Many factors, such as the patrons’ new Renaissance way of thinking (Ercole I d’Este and the nobility of Ferrara) and the multilateral, especially venetian, experience of artists (Pietro Benvenuti dagli Ordini, Biaggio Rossetti) contributed to the birth and formation of Ferrara Renaissance palace.Here we deal with some characteristics of the 15th century Venetian architecture introduced in Ferrara case during the period in question, especially those which: 1) seem to be out of tune with new Renaissance language spread in Northern Italy, in Emilia-Romagna, and Lombardia; 2) aspects, not common in the Renaissance architecture of Italian Quattocento as a whole; 3) introducing a possibility of artistic influence of Venice itself and that of the eastern lands of Levant drawn into the realm of Venetian cultural and commercial interests.The points in focus include the problems of wall surface decoration, cornices, staircases, balconies, as well as their formal transformation when applied to the houses of Ferrara (palazzo Schifanoia (14th–15th centuries), casa Romei (after 1442), palazzo Prosperi-Sacrati (after 1442).The points touched upon in the article enable one to see the Renaissance palace architecture of Ferrara as aunique part of the greater Mediterranean cultural area.